The Political Behavior of Local Politicians According to People’s Opinions in Kudyaluan Subdistrict, Trakanphuetphon District, Ubon Ratchathani Province - Khemakamo (Sribun) , PhraAeknarin; Sawattha, Sutiphong; Promkun, Suraphon (Journal of Graduate MCU KhonKaen Campus, 2023)
The purposes of this research were: 1) to study the level of public opinion towards political behavior of local politicians in Kudyaluan Sub-district, Trakan Phuet Phon District, Ubon Ratchathani Province; 2) to compare the level of public opinion towards political behavior of local politicians of the people in Kudyaluan Sub-district and 3) to study the suggestions of political behavior of local politicians according to the opinions of the people in Kudyaluan Sub-district by applying the Four Gharvsa Dhamma. The sample group consisted of 359 people and 14 key informants. The tools used were a questionnaire and an interview form. The data were analyzed using social science software packages and contextual content analysis. The research results were as follows: 1) The overall level of public opinion towards political behavior of local politicians in Kudyaluan Sub-district, Trakan Phuet Phon District, Ubon Ratchathani Province was statistically rated at a high level ( = 3.81). In aspect consideration, the aspect with the highest mean was political behavior in terms of personality traits ( = 3.95), followed by human relations ( = 3.93), sacrificing for the community ( = 3.90), morality ( = 3.87) and political behavior in leadership ( = 3.73) 2) The comparative results of the level of public opinion towards political behavior of local politicians in Kudyaluan Sub-district indicated that the sample group with differences in sex, age, education level, occupation and average monthly income had different opinions on the political behavior of local politicians in Kudyaluan Subdistrict, Trakan Phuet Phon District, Ubon Ratchathani Province with the statistical significance level of 0.05. 3) Suggestions: (1) in terms of Sacca, should administer local affairs with honesty, integrity, transparency, and no corruption (2) In terms of Dama, should be humble, know how to adapt and correct their own shortcomings. (3) In terms of Khanti, should be patient, determined and responsible for their assigned duties. (4) In terms of Cga, should be dedicated to their work by considering the overall idea.